2017
DOI: 10.1177/1753193417737920
|View full text |Cite
|
Sign up to set email alerts
|

Results of heterodigital flexor digitorum profundus hemi-tendon transfer for 23 flexor tendon injuries in zones 1 or 2

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The tensile strength of sutures is also an important aspect of tendon repair because it is the basis of a strong repair of the tendons that resists gapping or breakage at the repair site. [37][38][39][40][41][42][43][44] Lowstrength sutures easily lead to postoperative rupture and should always be avoided. [37][38][39][40][41][42][43][44] The tensile strengths of two modified sutures (Ethicon and PDS II) were tested with a mechanical testing instrument, and no significant change was found in tensile strengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile strength of sutures is also an important aspect of tendon repair because it is the basis of a strong repair of the tendons that resists gapping or breakage at the repair site. [37][38][39][40][41][42][43][44] Lowstrength sutures easily lead to postoperative rupture and should always be avoided. [37][38][39][40][41][42][43][44] The tensile strengths of two modified sutures (Ethicon and PDS II) were tested with a mechanical testing instrument, and no significant change was found in tensile strengths.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44] Lowstrength sutures easily lead to postoperative rupture and should always be avoided. [37][38][39][40][41][42][43][44] The tensile strengths of two modified sutures (Ethicon and PDS II) were tested with a mechanical testing instrument, and no significant change was found in tensile strengths. The results show that this modification method does not affect the mechanical properties of the sutures.…”
Section: Discussionmentioning
confidence: 99%
“…104 Bommier et al reported on 23 patients with single-stage hemi–flexor digitorum profundus tendon transfer for delayed or failed flexor digitorum profundus repairs. 107 Functional outcomes were excellent for 14 patients, good for seven, and poor for two. The advantages of the hemi–flexor digitorum superficialis or flexor digitorum profundus transfers are the use of an intrasynovial donor tendon with similar excursion.…”
Section: Isolated Flexor Digitorum Profundus Injuriesmentioning
confidence: 92%